Peptide Immunotherapy for Type 1 Diabetes—Clinical Advances - Smith, Emma L.; Peakman, Mark (Frontiers in Immunology, 2018)
Autoimmune and allergic diseases occur when an individual mounts an inappropriate immune response to a self-antigen, or an innocuous environmental antigen. This triggers a pathogenic T cell response resulting in damage to specific tissues and organs. In type one diabetes this manifests as destruction of the insulin-secreting  cells, resulting in a life-long dependency on recombinant insulin. Modulation of the pathogenic T cell response with antigen-specific peptide immunotherapy offers the potential to restore the immune homeostasis and prevent further tissue destruction. Recent clinical advances with peptide therapy approaches in both type 1 diabetes and other diseases are beginning to show encouraging results. New technologies targeting the peptides to specific cell types are also moving from preclinical development to the clinic. Whilst many challenges remain in clinical development, not least selection of the optimal dose and dosing frequency, this is clearly becoming a very active field of drug development.